2021
DOI: 10.1111/rssa.12679
|View full text |Cite
|
Sign up to set email alerts
|

Health Aid, Governance and Infant Mortality

Abstract: Any opinions expressed in this paper are those of the author(s) and not those of IZA. Research published in this series may include views on policy, but IZA takes no institutional policy positions. The IZA research network is committed to the IZA Guiding Principles of Research Integrity. The IZA Institute of Labor Economics is an independent economic research institute that conducts research in labor economics and offers evidence-based policy advice on labor market issues. Supported by the Deutsche Post Founda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 82 publications
(143 reference statements)
0
13
0
Order By: Relevance
“…All of these questions face the problem of endogeneity between aid and the variable of interest. Our instrument is well suited to address this problem, as has been demonstrated in Bluhm et al (2020) for conflict, Ziaja (2017) for democracy, Doucouliagos et al (2019) for infant mortality and Dreher et al (2019) for refugees. In providing an instrumental variable that is suitable to address the endogeneity of aid in a broad setting of questions, we hope to contribute in providing a more nuanced understanding of the various causal effects the aid might have.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All of these questions face the problem of endogeneity between aid and the variable of interest. Our instrument is well suited to address this problem, as has been demonstrated in Bluhm et al (2020) for conflict, Ziaja (2017) for democracy, Doucouliagos et al (2019) for infant mortality and Dreher et al (2019) for refugees. In providing an instrumental variable that is suitable to address the endogeneity of aid in a broad setting of questions, we hope to contribute in providing a more nuanced understanding of the various causal effects the aid might have.…”
Section: Discussionmentioning
confidence: 99%
“…() for conflict, Ziaja () for democracy, Doucouliagos et al. () for infant mortality and Dreher et al. () for refugees.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… GDP per capita is an indicator of economic development and a predictor of both IMR and domestic health expenditure (Lordan et al, 2011; Mishra & Newhouse, 2009; Wilson, 2011). Population size is an indicator of total need, total DAH disbursements, and its inclusion in aid effectiveness models is standard even when DAH and infant mortality are expressed in per population terms (Doucouliagos et al, 2021; Mishra & Newhouse, 2009). Past research has indicated fertility patterns influence IMR, thus fertility rate was included (Mishra & Newhouse, 2009).…”
mentioning
confidence: 99%
“… An extended model includes a set of additional control variables that are potentially important time‐varying determinants of IMR but—because of their potential role in mediating the relationship between DAH (and/or SWAp) and IMR—may bias downwards our estimates of DAH (and SWAp) effects. For example, government effectiveness and corruption control may constitute necessary pre‐conditions for aid effectiveness (Burnside & Dollar, 2000; Doucouliagos et al, 2021) but DAH may also have unintended (negative) consequences for good governance (Dijkstra, 2018). HIV prevalence may impact directly on IMR (Kurewa et al, 2010) and may distort allocation of DAH (Lordan et al, 2011).…”
mentioning
confidence: 99%